1990
DOI: 10.1038/ki.1990.147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parathyroid hormone on human T cell activation

Abstract: Lymphocytes have receptors for PTH and patients with chronic renal failure have high blood levels of PTH and impaired lymphocyte function. It is possible, therefore, that PTH affects lymphocyte function. We studied the interaction between PTH and proliferation of human lymphocytes in vitro and examined potential mechanisms for such an interaction. 1-84 PTH stimulated in a dose dependent manner PHA-induced proliferation of T cells but had no effect on PWM-induced proliferation. The hormone did not alter CD4/CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 50 publications
0
46
2
Order By: Relevance
“…Klinger et al [33] found that in hemodialysis patients, parathormone augmented T-cell proliferation induced by PHA as well as interleukin 2 production by these cells [34], CAPD patients lose macrophages and proteins in cluding immunoglobulins with the peritoneal effluent [35]. The loss of immunoglobulins represents about 15 % of the total amount of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Klinger et al [33] found that in hemodialysis patients, parathormone augmented T-cell proliferation induced by PHA as well as interleukin 2 production by these cells [34], CAPD patients lose macrophages and proteins in cluding immunoglobulins with the peritoneal effluent [35]. The loss of immunoglobulins represents about 15 % of the total amount of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with renal failure-related hyperparathyroidism have impaired humoral immunity, including reduced B cell proliferation and antibody production [43]. Lymphocytes have receptors for PTH [44], and it has been reported that PTH inhibits production of IgG, IgA and IgM by cultured human B cells, while the inactivation of PTH abolishes this inhibitory effect [45]. The respective contributions of these various mechanisms to immune dysfunction in patients with hyperparathyroidism need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In 65,115,116 (ii) elevated [Ca 2+ ] i and total Ca 2+ concentration of PBMC in response to ALDOST and which occurs before tissue invasion, together with increased H 2 O 2 production by monocytes and lymphocytes; 65 (iii) PTH regulated T-cell activation; [117][118][119][120] (iv) parathyroidectomy prevented PBMC Ca 2+ overloading and vascular lesions; 83,84 (v) upregulated expression of antioxidant defenses in these cells; and (vi) prevention of Ca 2+ loading and oxi/nitrosative stress by cotreatment with either Spiro or an antioxidant. 13,65,116 The presence of oxi/nitrosative stress at a systemic level in these models is evidenced by increased serum levels of thiobarbituric acid-reacting substances and reduced activity of plasma a 1 -antiproteinase.…”
Section: Cellular and Molecular Pathways Leading To Proinflammatory Cmentioning
confidence: 99%